ANALISIS STRATEGI PEMASARAN DIGITAL UNTUK MENINGKATKAN PENJUALAN PRODUK TIKAR MENDONG MEKAR PUTRA - Nurhayaty, Maria; Sutrisna , Dedi; Martha , Taufik (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2022)
This study aims to find out 1) digital marketing applied by Tikar mendong Mekar Putra, 2) the role of digital marketing in increasing sales of Tikar Mendong Mekar Putra, and 3) identifying strengths, weaknesses, opportunities, and threats available using SWOT analysis. The method used in this study is qualitative-descriptive research, namely research based on the strength of analytic descriptions. Data collection is done by interview, observation, and documentation. While data analysis uses SWOT analysis. The results of the study reveals that Tikar Mendong Mekar Putra practices digital marketing strategies (online marketing) through social media such as Facebook, instagram, and other internet networks that are connected with wider consumer reach since 2017. Tikar Mendong Mekar Putra cooperates with Zalora, a market place for online media sales that can be accessed globally. The application of digital marketing by Tikar Mendong Mekar can increase sales. This is so because consumers are wider, closer, can check the quality and reputation of the product, and can make transactions online.